The effects of melatonin and potassium fertilizer on fruit yield and quality of ‘Haruhi’ strawberry under two light conditions - Nurizqia, Ghaida Marsha; Farida, Farida; Hindersah, Reginawanti; Endo, Kenji; Budiarto, Rahmat; Mubarok, Syariful (Universitas Padjadjaran, 2026)
Strawberry (Fragaria × ananassa) ‘Haruhi’ is a subtropical plant that is being cultivated in Indonesia. High temperatures in tropical climates could decrease strawberry yield and fruit quality. The purpose of this study was to evaluate the effect of light, melatonin, potassium fertilizers, and their interactions on the yield and fruit quality of ‘Haruhi’ strawberry. This research was conducted from April to June 2024 at the Bale Tatanen, Faculty of Agriculture, Universitas Padjadjaran. A split-plot design was used, with lighting treatment as the main plot and melatonin and potassium fertilizer treatments as the subplot. Lighting treatments consisted of supplemental LED lighting and natural light (non-LED). Subplot treatments included control, 100 μM melatonin, 2 g L⁻¹ potassium fertilizer, and their combination. The results showed that the combination of non-LED lighting with melatonin and potassium fertilizer produced the best fruit diameter and fruit weight. Under non-LED lighting, melatonin treatment resulted in the highest total soluble solids, while the control treatment produced the highest number of flowers. The interaction between LED lighting and melatonin resulted in the highest fruit number. Non-LED lighting alone also produced the best plant height, leaf number, and fruit length. Potassium fertilizer alone resulted in the highest leaf number, while the control treatment produced the highest plant height.